Sistema de monitoramento da invasão de vegetação em linhas de transmissão usando redes de sensores sem fio - Medeiros, Túlio Ítalo Oliveira de (2018)
Accidents provoked by vegetation encroachment in power lines located in urban and rural areas are common causes of interruption in electricity supply in Brazil. This work presents a novel monitoring system for measuring the vegetation encroachment around transmission lines and proposes a mathematical model for the problem. The proposed system is based on a Wireless Sensor Network (WSN) in which a set of sensor nodes is sequentially deployed along a large transmission power line. The main objective of the proposed measurement system is to assess the vegetation encroachment by means of the signal power decay between two consecutive sensor nodes. The lesser the received power between two sensor nodes, the larger is the vegetation encroachment. Experimental measurements showed that it is possible to perform the detection through the use of RSSFs and validated the mathematical model of the signal power lloss.